2016
DOI: 10.4055/cios.2016.8.3.254
|View full text |Cite
|
Sign up to set email alerts
|

Are Western Knee Designs Dimensionally Correct for Korean Women? A Morphometric Study of Resected Femoral Surfaces during Primary Total Knee Arthroplasty

Abstract: BackgroundThe purpose of this study was to determine the shape of the distal femur of Korean women compared with the prostheses currently available in Korea.MethodsMorphometric data (5 parameters) were measured in 356 resected femurs of Korean women undergoing primary total knee arthroplasty (TKA) utilizing the LCS knee implant (DePuy). The data were then compared with 5 additional contemporary TKA implant systems.ResultsImplant designs based on Caucasian population data do not ideally match the distal femoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…This corroborates the findings of numerous studies that found women to have narrower knees [2, 19, 22, 25, 28, 39], though it is worth noting that some found no difference in aspect ratio between the sexes [27, 33]. Gender‐specific ‘narrow’ implants may thus alleviate some of the mediolateral overhang commonly reported in women [2, 21, 33], though they are not always sufficient to improve outcomes of TKA [11, 12, 37]. More recent studies also reported that Asians had wider knees than Caucasians [19, 22, 28], though others found no such difference [27, 39].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This corroborates the findings of numerous studies that found women to have narrower knees [2, 19, 22, 25, 28, 39], though it is worth noting that some found no difference in aspect ratio between the sexes [27, 33]. Gender‐specific ‘narrow’ implants may thus alleviate some of the mediolateral overhang commonly reported in women [2, 21, 33], though they are not always sufficient to improve outcomes of TKA [11, 12, 37]. More recent studies also reported that Asians had wider knees than Caucasians [19, 22, 28], though others found no such difference [27, 39].…”
Section: Discussionsupporting
confidence: 88%
“…The present study was based on CT scans and reported multivariable analyses that control for confounding factors, while that of Mahfouz et al used magnetic resonance images, which can be less detailed when rendering bony structures, and presented basic univariable analyses, that do not control for confounding factors such as size. The present findings, therefore, affirm that Asian women have the highest asymmetry ratios, indicating once more, that this subgroup is the most likely to exhibit bone-implant mismatch [21,33].…”
Section: Discussionsupporting
confidence: 81%
“…After the completion of the experimental procedure, all participants underwent TKA with the same type of high-flexion mobile prosthesis (Implantcast; GMBH Lüneburger Schanze, Buxtehude, Germany) with cement using a tricompartmental, minimally invasive quadriceps-sparing technique [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…36 This is further illustrated through the design of total knee arthroplasty, which is primarily designed for the White population anatomy, which is sufficiently different from that of the Korean population. 37 This provides additional credence to the notion that subanalysis of a patients demographics is integral when understanding the efficacy of new medical devices.…”
Section: Discussionmentioning
confidence: 91%